Investigating the Algodones Dune Field of Southern California I : Overview and Geomorphic History of a Dynamic Erg [Sand Dune Field] - Turner, Anna; Niesen, Katelyn; Kough, Kaisa; Limber, Taylor; Dilkowski, Hunter; Goettl, Martin; Jol, Harry M. (My University, 2019)
The Algodones Erg [Sand Dune Field] is in the Sonoran Desert and span over 72420.5 meters in length and 9656 meters in width. It is a complex and understudied erg system with a rich geomorphic history and relationship to the ancient Lake Cahuilla. The purpose of the study is: to collect data to understand the sediments below the dunes to determine the relationship between the dunes and the ancient Lake Cahuilla, and to explore the relationship between human impacts and management on the dune system. Examining the relationship between the ancient Lake Cahuilla and the dune field will further our understanding of the surrounding landscapes and various geologic time periods. The knowledge collected will provide insight on potential impacts to communities and water systems in the region of study. Using ground penetrating radar, laser leveling, subsurface imaging, and an unmanned aerial vehicle, data was collected to analyze the relationship between Lake Cahuilla and the Algodones Dunes. Upon analysis of the data collected, this dune complex continues to be studied for further impacts on communities and land management.
Color poster with text, images, photographs, and maps.
Keywords: Sand dunes; Landform evolution; Sediments; Posters